Exercise as airway clearance therapy (ExACT) in cystic fibrosis: a UK-based e-Delphi survey of patients, caregivers and health professionals. Issue 1 (9th September 2022) - Saynor, Zoe Louise; Cunningham, Steve; Morrison, Lisa; Main, Eleanor; Vogiatzis, Ioannis; Reid, Simon; Urquhart, Donald
Abstract : Replacing traditional airway clearance therapy (tACT) with exercise (ExACT) in people with cystic fibrosis (pwCF) is a top research priority. A UK-based e-Delphi consensus was performed to inform the type(s), duration and intensity of ExACT. The expert panel comprised CF physiotherapists, doctors, pwCF and parents/partners. Exercise ACT was considered to be aerobic activity, of at least 20 min duration and intense enough to elicit deep breathing. Consensus was reached that assessment breaths, coughs and huffs should accompany exercise to remove loose secretions, with support for trials to investigate ExACT versus tACT during times of stable disease but not pulmonary exacerbations.